CHALLENGING INEQUALITY: ANALYZING THE PORTRAYAL OF BLACK WOMEN WORKERS IN 'SELF MADE' THROUGH FEMINIST STYLISTIC LENS - Wulan, Annisa Sri; Degaf, Agwin (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
The physical appearance, particularly beauty standards influenced by social constructs, significantly impacts a woman's self-esteem and employment opportunities. Regrettably, black women, particularly African-American women, often experience marginalization due to societal beauty standards, racial biases, and gender discrimination within patriarchal settings. In light of this, our research employs the miniseries